Design and Implementation of IoT Arduino Based Microcontroller of Circuit Breaker for Distribution Side - R. Sowmiya,; Er. J. Jayakumar,; Dr. S. Sivasakthi, (International Journal of Scientific Research in Computer Science, Engineering and Information Technology, 2024)
In the modern industrial environment, ensuring the safety of workers and minimizing operational risks are paramount. This project presents an IoT-Driven OTP Authentication System designed to enhance safety and control in managing circuit breakers. The system leverages Arduino-based automation combined with OTP (One-Time Password) authentication to regulate access to circuit breakers, addressing the rising concerns of human errors and accidents. The proposed system integrates a microcontroller-based circuit breaker control mechanism with an OTP authentication process. When maintenance personnel need to operate or access the circuit breaker, they must enter a time-sensitive OTP via a keypad. This OTP is generated and sent through an embedded system, ensuring secure and restricted access. Additionally, the system incorporates IoT technology, allowing access control and monitoring via a dedicated Android application. By implementing this solution, the project aims to streamline operations, reduce the likelihood of unauthorized access, and improve overall worker safety. The combination of OTP authentication and IoT connectivity ensures robust security measures and facilitates real-time monitoring and management of circuit breaker operations. This innovative approach not only enhances the efficiency of maintenance procedures but also contributes to a safer working environment by preventing accidents and unauthorized interventions.
Keywords: OTP Authentication; IoT Integration; Automated Circuit Breaker; Worker Safety Embedded Systems; Arduino Control